2018
DOI: 10.1177/0192623318778796
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Disc Shedding and Phagocytosis of Photoreceptor Outer Segment Contributes to Kava Kava Extract–induced Retinal Degeneration in F344/N Rats

Abstract: There was a significant increase in the incidence of retinal degeneration in F344/N rats chronically exposed to Kava kava extract (KKE) in National Toxicology Program (NTP) bioassay. A retrospective evaluation of these rat retinas indicated a similar spatial and morphological alteration as seen in light-induced retinal degeneration in albino rats. Therefore, it was hypothesized that KKE has a potential to exacerbate the light-induced retinal degeneration. To investigate the early mechanism of retinal degenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
2
2
0
Order By: Relevance
“…In CCs, high levels of MT modify the intracellular organelles, intracellular membrane structure, and thus their lysosome functions, which directly affects their phagocytosis and autophagy [ 63 ]. These observations are supported by previous reports of MT effects on phagocytosis, autophagy, and mitophagy [ 64 , 65 , 66 ]. MF analysis indicated that MT mainly affected protein and enzyme bindings and their functions.…”
Section: Discussionsupporting
confidence: 92%
“…In CCs, high levels of MT modify the intracellular organelles, intracellular membrane structure, and thus their lysosome functions, which directly affects their phagocytosis and autophagy [ 63 ]. These observations are supported by previous reports of MT effects on phagocytosis, autophagy, and mitophagy [ 64 , 65 , 66 ]. MF analysis indicated that MT mainly affected protein and enzyme bindings and their functions.…”
Section: Discussionsupporting
confidence: 92%
“…Reduction of the photoreceptor layer has been previously described in rat models of LIRD, such as F344/N rats and albino Sprague Dawley rats. 39 , 40 In our study, as expected, at high illuminance (i.e., 3000 lux), a significant reduction of photoreceptor layer thickness was found in two experimental groups, especially in the CL-3000 group, which had a lower thickness and the appearance of disordered and sparse photoreceptor segments all over the retina. At standard writing illuminance (i.e., 300 lux), retinal damage was observed in the CL-300 group, which induced a statistical reduction in the thickness of the photoreceptor layer.…”
Section: Discussionsupporting
confidence: 86%
“…In a subsequent study, the group demonstrated that F344N rats dosed with KKE 1.0 g/kg for 90 days did not show signs of retinal degeneration. However, the RPE, only from the superior retina, had a reduced number of phagosomes [ 60 ]. The authors speculated that this result could indicate an impairment in photoreceptor outer segment phagocytosis by RPE cells, which could affect the health of the retina after the 2-year exposure observed in the previous study.…”
Section: Natural Productsmentioning
confidence: 99%